Assessment of urinary tract infection and their resistance to antibiotics in diabetic and non-diabetic patients (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Diabetic patients are more susceptible to urinary tract infections (UTIs) than non-diabetic patients and due to the development of multidrug resistant uropathogenic strains, the choice of antibacterial agents is being limited. The study was undertaken to determine the influence of diabetes mellitus on the uropathogens and antibiotic sensitivity pattern among patients with UTIs. A cross-sectional study was conducted in which total of 400 patients were studied out of which 150 were diabetics and 250 were non-diabetics. Patients with negative urine culture (n = 240) were excluded from the study and 160 patients with positive culture of UTIs of which 80 were diabetics and 80 were non-diabetics, included in this study. Clinical data were obtained from individual study participant with informed written consent using pre-tested questionnaire. According to the clean-catch procedure, midstream urine samples were collected and cultured for the diagnosis and susceptibility of bacteriuria. Out of 160 uropathogenic isolates, E. coli was found as a leading pathogen i.e. 46.25% followed by Candida spp. 30.62%, S. Faecalis 15.62%, P. aeruginosa 3.13%, Pneumococcus. 1.25%, MSSA 1.25%, MRSA 0.63%, Proteus spp. 0.63% and Vancomycin resistant enterococcus spp. 0.63%. The results indicated that prevalence of UTIs was significantly higher in diabetic patients than in non-diabetic subjects. E. coli was found to be the most common isolate. It was observed that UTIs in diabetic patients was more in female diabetic patients than in male patients. Investigation of bacteriuria in diabetic patients for UTIs is an important tool for the treatment and prevention of renal complications.